2022
DOI: 10.1186/s12872-022-02942-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum LDL-C/HDL-C ratio and the risk of carotid plaques: a longitudinal study

Abstract: Background Dyslipidemia contributes to an increased risk of carotid atherosclerosis. However, the association between the ratio of low-density lipoprotein cholesterol (LDL-C) to high-density lipoprotein cholesterol (HDL-C) and carotid plaque formation has not been well documented. This study aims to assess the role of LDL-C/HDL-C in the risk of carotid plaque formation in a Chinese population. Methods We followed 2,191 participants who attended the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Zhuchao et al investigated the role of the LDL-C/HDL-C ratio on carotid plaque formation. The researchers screened 2191 participants and noted that carotid plaque formation increased as the LDL-C/HDL-C ratio increased, particularly in people with diabetes and dyslipidemia [ 26 ]. These studies are evidence that the LDL-C/HDL-C ratio is an indicator of atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhuchao et al investigated the role of the LDL-C/HDL-C ratio on carotid plaque formation. The researchers screened 2191 participants and noted that carotid plaque formation increased as the LDL-C/HDL-C ratio increased, particularly in people with diabetes and dyslipidemia [ 26 ]. These studies are evidence that the LDL-C/HDL-C ratio is an indicator of atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…T Sun et al compared patients and healthy controls, the LDL-C/HDL-C ratio was higher in patients with CAD (2.94 ± 1.06 vs. 2.36 ± 0.78, p < 0.05). They clari ed that the LDL-C/HDL-C ratio is more valuable than LDL-C and HDL-C levels alone in lipid panel analysis in determining the severity of coronary artery disease [4] .In 2000, it was proposed that the observation of the therapeutic effect of statins should focus on LDL-C/HDL-C, rather than only the concentration changes of LDL-C and HDL-C paraments only [23] .Zhuchao found that when LDL-C/HDL-C ratio increased,the carotid plaque increased, LDL-C/HDL-C ratio was a mojor risk factor on carotid plaque,especially in patients with dyslipidemia and diabetes [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The LDL-C/HDL-C ratio is reported to be a more valuable biomarker than LDL-C or HDL-C levels alone, especially for predicting the risk of multiple diseases. If the ratio is low, atherosclerosis risk factors are reduced [46][47][48]. Based on the experimental results obtained from the sugar-free fermentation method and fermentation cycle, the hypolipidemic effect of FLJ on the hyperlipidemic hamster model was investigated.…”
Section: Discussionmentioning
confidence: 99%